Kajian Pustaka Peran Mindfulness dalam Mengatasi Stress Akademik Mahasiswa Pascasarjana - Leo Nando Sastro; Shintia Greshia; Sukmana Djaya; Citra Agustin Gutami; Kemanya Karbono (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
Academic stress is one of the main challenges experienced by postgraduate students due to complex academic workloads, such as thesis writing, scientific publications, work demands, and personal roles. This condition can trigger emotional exhaustion, decreased concentration, anxiety, and burnout. This study used the Systematic Literature Review (SLR) method to analyze the role of mindfulness as a stress management strategy in college students. The literature analyzed included studies from 2020–2025 that examined the relationship between mindfulness and academic stress, including interventions based on Mindfulness-Based Stress Reduction (MBSR) and Mindfulness-Based Cognitive Therapy (MBCT). The study results showed that mindfulness has a significant effect on reducing academic stress, improving emotional regulation, learning focus, sleep quality, and psychological well-being. Mindfulness also helps students build resilience and develop adaptive mindsets in dealing with academic pressure. These findings confirm that mindfulness can be an effective and applicable strategy in supporting the mental health of postgraduate students.